Heat and mass transfer in binary film evaporation and condensation in vertical channel - Nasr, Abdelaziz; S. Al-Ghamdi, Abdulmajeed (International Journal of Engineering and Technology, 2015)
Evaporation and condensation in the presence of binary liquid film flowing on one of two parallel vertical plates by mixed convection have been studied numerically. The first plate is adiabatic and wetted by a binary liquid film while the second one is dry and isothermal. The results concern the effects of the inlet parameters on the ethylene glycol evaporation and on the water condensation. Results obtained show that the increase of the inlet vapor concentration of water benefits its condensation and the increase of the inlet vapor concentration of ethylene glycol inhibits its evaporation.